Rethinking Practices by Rethinking Expertise: A Relational Approach to Family-Centred Inclusive Services - Jóna G. Ingólfsdóttir; Rannveig Traustadóttir; Snæfríður Þóra Egilson (Scandinavian Journal of Disability Research, 2021)
This article focuses on the views and experiences of professionals providing specialised services to disabled children and their families. It is part of a larger research project that investigates the gap between policy ideals and service provision for young disabled children and their families in Iceland. Contrary to official policies, earlier findings based on the families’ perspectives reported strain and stress from fragmented and inflexible services. The findings presented here are based on three focus-group interviews, conducted with 13 professionals from six disciplines. The aim was to capture their views on their roles, responsibilities, and working conditions. A number of organisational and professional barriers were exposed along with an overall lack of awareness of the basic principles of family-centred services and the human rights relational approach to disability. Recommendations for service development are inspired by Edwards’ relational theory about building inter-professional and inter-organisational links to create high quality practices.